In Vivo Targeting Replication Protein A for Cancer Therapy - VanderVere-Carozza, Pamela S.; Gavande, Navnath S.; Jalal, Shadia I.; Pollok, Karen E.; Ekinci, Elmira; Heyza, Joshua; Patrick, Steve M.; Masters, Andi; Turchi, John J.; Pawelczak, Katherine S. (Frontiers in Oncology, 2022)
Replication protein A (RPA) plays essential roles in DNA replication, repair, recombination and the DNA-damage response (DDR). Retrospective analysis of lung cancer patient data demonstrates high RPA expression as a negative prognostic biomarker for overall survival in smoking-related lung cancers. Similarly, relative expression of RPA is a predictive marker for response to chemotherapy. These observations are consistent with the increase in RPA expression serving as an adaptive mechanism that allows tolerance of the genotoxic stress resulting from carcinogen exposure. We have developed second generation RPA inhibitors (RPAi’s) that block the RPA-DNA interaction and optimized formulation for in vivo analyses. Data demonstrate that unlike first generation RPAi’s, second generation molecules that show increased cellular permeability and induce cell death via apoptosis. Second generation RPAi’s elicit single agent in vitro anticancer activity across a broad spectrum of cancers and the cellular response suggests existence of a threshold before chemical RPA exhaustion induces cell death. Chemical RPA inhibition potentiates the anticancer activity of a series of DDR inhibitors as well as traditional DNA damaging cancer therapeutics. Consistent with chemical RPA exhaustion, we demonstrate that the effects of RPAi on replication fork dynamics are similar to other known DDR inhibitors. An optimized formulation of RPAi NERx329 was developed that resulted in single agent anticancer activity in two non-small cell lung cancer models. These data demonstrate a unique mechanism of action of RPAi’s eliciting a state of chemical RPA exhaustion and suggest they will provide an effective therapeutic option for difficult to treat lung cancers.